2020
DOI: 10.18502/ijm.v11i6.2218
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of antibiotic resistance among uropathogens in Aljouf region northern Saudi Arabia

Abstract: Background and Objectives: Urinary tract infections are common health problem affecting millions worldwide. Antibiotic resistance among uropathogens (Ups) is prevalent in many countries. In the absence of any available data in the region, this hospital-based study investigated the pattern, frequency and susceptibility of Ups at Prince Mutaib Bin Abdulaziz Hospital, Aljouf Region, Saudi Arabia. Materials and Methods: A retrospective assessment of UPs and their antibiotics susceptibility was conducted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…The tested Gram-negative isolates recovered from UTI patients in Ha’il showed great sensitivity to amikacin, and this outcome is matched with data of a similar investigation in Al-Jouf, Saudi Arabia. 39 Accordingly, amikacin is one of the promising candidates to be considered for use as a first-line drug for treating patients with UTIs in Ha’il and Al-Jouf regions of Saudi as well as other areas with similar trends.…”
Section: Discussionmentioning
confidence: 99%
“…The tested Gram-negative isolates recovered from UTI patients in Ha’il showed great sensitivity to amikacin, and this outcome is matched with data of a similar investigation in Al-Jouf, Saudi Arabia. 39 Accordingly, amikacin is one of the promising candidates to be considered for use as a first-line drug for treating patients with UTIs in Ha’il and Al-Jouf regions of Saudi as well as other areas with similar trends.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO has reported that an estimated 50% of women experience a UTI at some point in their lives [18]. We found 18 papers that studied UTIs in adults, especially in women, as they experienced more infections than men [2,13,18,24,[26][27][28][29][30]32,33,36,40,43,49,55,58,60]. Adult patients were the most represented in all the studies.…”
Section: Uti In Adultsmentioning
confidence: 99%
“…The most commonly isolated organisms were E. coli, followed by Klebsiella spp., P. aeruginosa S. agalactiae, E. faecalis, Streptococcus group B and D, methicillin-resistant Staphylococcus Aureus (MRSA), and vancomycin-resistant E. faecalis (VRE). Some studies even reported a significantly higher prevalence of UTI caused by E. coli among women (p < 0.05) [2,13,18,24,[26][27][28][29][30]32,33,36,40,43,49,55,58,60].…”
Section: Uti In Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted in 2013 at Armed Forces Hospital Southern Region (AFHSR), Khamis Mushayt, Saudi Arabia, showed nitrofurantoin had a resistance rate of 25% & 30% against E. coli and other Gram-negative bacteria, respectively [ 6 ]. Another recent study conducted in 2017 at Prince Mutaib bin Abdulaziz Hospital, Aljouf Region, Saudi Arabia, showed a resistance rate for fosfomycin and nitrofurantoin of 24.6% and 42.9%, respectively, against common Gram-negative uropathogens [ 7 ].…”
Section: Introductionmentioning
confidence: 99%